Customer Satisfaction Mediates Service Quality And Price Perception On Customer Loyalty - Hardian, Hardian (Publisher Cv. Inara, 2025)
The present study aims to analyse the effect of service quality and price perception on loyalty, as mediated by customer satisfaction, in the context of the selection of educational institutions by parents of students. The study adopts a quantitative approach, utilising a survey method, and involves 181 respondents who are parents of students. These respondents were selected through a purposive sampling technique. The data collection was conducted through a Google Form-based questionnaire, while data analysis employed the Structural Equation Modeling (SEM) method, utilising WarpPLS V.8 software. The results of the analysis demonstrate that service quality and price perception exert a substantial influence on parental satisfaction and loyalty. The study concluded that good service quality fosters trust and satisfaction, while reasonable price perception fosters long-term loyalty. The findings of this study corroborate the significance of service and pricing strategies in enhancing learner retention.